2021
DOI: 10.3389/fagro.2021.664034
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Evolution of Invasive Weeds Under Climate Change: Present Evidence and Future Research Needs

Abstract: Although evolution has been often seen as a gradual process through a Darwinian lens, far more rapid evolutionary change has been observed in recent times. Recent examples documenting the potential speed of invasive plant evolution have included: latitudinal flowering clines, life history shifts, or abrupt changes in morphology. The timescales for such observations range from centuries down to <5 years. Invasive weeds provide good models for the rapid changes, partly because invasive weeds exhibit uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 129 publications
(220 reference statements)
1
35
0
3
Order By: Relevance
“…Whereas phenotypic plasticity may increase the ecological niche breadth of the species, post-introduction or post-colonization rapid evolution is known to produce genetically based phenotypic variations and adaptations, which can increase plant invasiveness. Therefore, phenotypic plasticity and rapid adaptation may be considered key components of the release–naturalization–invasion continuum [ 55 ]. In recent studies, common ragweed has been observed to grow in new areas at high altitude (over 1200 m) as a casual species; however, it seems that the species is not still able to establish at the current climatic conditions [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas phenotypic plasticity may increase the ecological niche breadth of the species, post-introduction or post-colonization rapid evolution is known to produce genetically based phenotypic variations and adaptations, which can increase plant invasiveness. Therefore, phenotypic plasticity and rapid adaptation may be considered key components of the release–naturalization–invasion continuum [ 55 ]. In recent studies, common ragweed has been observed to grow in new areas at high altitude (over 1200 m) as a casual species; however, it seems that the species is not still able to establish at the current climatic conditions [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is possible that Rumex spp. have rapidly adapted to tolerate the climates available in both North America and New Zealand (Bates & Bertelsmeier, 2021;Boheemen et al, 2019;Clements & Jones, 2021;Hulme & Barrett, 2013;Luo et al, 2019), though Rumex spp.…”
Section: Congeners Display Similar Niche Shift Directions But Low Ove...mentioning
confidence: 99%
“…Поширення інвазійних видів у природі не має географічних меж [2; 11]. У карантинних бур'янів сформовано унікальні еволюційні механізми, що сприяють змінам їх онтогенезу й морфології, забезпечуючи значну пластичність та адаптивні властивості [16]. Інвазійні рослини характеризуються зазвичай спільними біологічними ознаками щодо високого репродуктивного потенціалу й толерантності до стресових факторів.…”
Section: аналіз останніх досліджень і публікаційunclassified
“…На інвазію рослин та їхнє подальше існування в новій зоні впливають кліматичні, геологічні, ґрунтові умови, наявність доступної вологи та інші фактори [11]. Зміни температури, режимів зволоження та екстремальні кліматичні умови діють на всі рослини, але карантинні види порівняно із місцевими зазвичай краще пристосовані до їх впливу [16]. Інвазійні рослини здатні зменшити кількість світла, води, поживних речовин і простору, доступного для місцевих видів, змінити водно-фізичні та хімічні властивості ґрунту, зокрема вбирну здатність, стійкість до ерозії тощо [17; 18].…”
Section: аналіз останніх досліджень і публікаційunclassified